Yamabe Solitons and Ricci Solitons on Almost co-Kähler Manifolds. Issue 3 (September 2019) - Suh, Young Jin; De, Uday Chand
Abstract: The object of this paper is to study Yamabe solitons on almost co-Kähler manifolds as well as on $(k, \unicode[STIX]{x1D707})$ -almost co-Kähler manifolds. We also study Ricci solitons on $(k, \unicode[STIX]{x1D707})$ -almost co-Kähler manifolds.